1983
DOI: 10.7326/0003-4819-98-3-315
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Changes After Weight Reduction in Obesity Hypertension

Abstract: Intravascular volumes and systemic and regional hemodynamic variables were measured before and after weight reduction in 12 patients with obesity and essential hypertension. These findings were compared with those in nine patients who did not have any weight loss. Reduction of mean arterial pressure significantly correlated with the fall in total body weight (r = 0.46, p less than 0.05). Total circulating and cardiopulmonary blood volumes were significantly reduced (p less than 0.05 and p less than 0.01, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
4
4

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(63 citation statements)
references
References 30 publications
4
51
4
4
Order By: Relevance
“…[51][52][53] Thus, it can be suggested that these factors may have contributed towards decreased antihypertensive drug use after loss of excessive weight due to the bariatric surgery.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…[51][52][53] Thus, it can be suggested that these factors may have contributed towards decreased antihypertensive drug use after loss of excessive weight due to the bariatric surgery.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Therefore, it is possible that the target organ for augmented sympathetic activity in obesity might be the kidney rather than the blood vessels. The observations that obesity is associated with volume overload and decreased peripheral resistance [Messerli, 1982], which are partly reversed by weight loss [Reisin et al, 1983], lend some support to this alternative hypothesis. Nevertheless, the present study does not provide evidence supporting this possibility because plasma renin activity was not different in obese and lean subjects and did not change after weight loss.…”
Section: Weight Lossmentioning
confidence: 59%
“…Il semblerait que ce soit une relation de cause à effet, en ce sens qu'une diminution du poids entraînerait du même coup une baisse de la pression sanguine (Reisin et al, 1983). Les personnes obèses dont la masse adipeuse se concentre dans le haut du corps sont plus susceptibles d'en souffrir, la pression exercée dans la région du coeur étant plus grande (Watanabe et Tochikubo, 2003).…”
Section: Hypertension Artérielleunclassified